Network monitoring system to detect unauthorized connection - A Hamid, Isredza Rahmi; Ab Sukor, Nurul Hatun; Mohd Foozy, Cik Feresa; Abdullah, Zubaile (RAZI Publishing, 2017)
The Network Monitoring System to Detect Unauthorized Connection is a network analytic tool that use to review local area network usage. The main purpose of the application is monitoring the internet protocol traffic between local area network and Internet. In addition, this system aimed to detect unauthorized Internet Protocol addresses that are inside the network range. It also can prevent network intruders from Local Area Network connection (LAN). It is a computerized system that complete with element of confidentiality, integrity and availability. The system was built using waterfall methodology that begins with system analysis, design, implementation, testing, installation and maintenance. The system is using Visual Studio 2013 with SQL Server as server operations. There are ten modules in this system which are user main page, register admin module, register staff module, login admin module, login staff module, admin menu module, staff menu module, scan view module, status view module and report module. There are about 30 respondents who agreed and satisfied with the system. As a result, this system was successfully built to detect and block the unauthorized access in the network.